2020
DOI: 10.1002/ijfe.2106
|View full text |Cite
|
Sign up to set email alerts
|

Boardroom gender diversity and dividend payout strategies: Effects of mergers deals

Abstract: Our study examines the effects of mergers and acquisitions deals on the relationship between female leadership and dividend strategies for 90 UK listed firms during the period 2006-2016. Results indicate that firms with a larger proportion of female directors serving on the board are more likely to pay higher dividends, but this positive finding is weaker when the firms experienced a higher number of mergers and acquisitions deals. Interestingly, extended analyses on female directors' positions show the opposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 76 publications
(107 reference statements)
5
15
0
Order By: Relevance
“…Bae et al (2012) asserted that a strong CG mechanism in firms is related to higher dividend payments and mitigates agency problems. Trinh et al (2020) also demonstrated a positive relationship between gender diversity and dividend payments. Diversity on the board affects its efficiency at different levels, for example, the individual level and the team level.…”
Section: Board Gender Diversity and Dividend Payoutsmentioning
confidence: 91%
See 2 more Smart Citations
“…Bae et al (2012) asserted that a strong CG mechanism in firms is related to higher dividend payments and mitigates agency problems. Trinh et al (2020) also demonstrated a positive relationship between gender diversity and dividend payments. Diversity on the board affects its efficiency at different levels, for example, the individual level and the team level.…”
Section: Board Gender Diversity and Dividend Payoutsmentioning
confidence: 91%
“…Bae et al (2012) asserted that a strong CG mechanism in firms is related to higher dividend payments and mitigates agency problems. Trinh et al (2020) also demonstrated a positive relationship between gender diversity and dividend payments. Finally, McGuinness et al (2015) provided positive but insignificant results in this context, while Mustafa et al (2020) showed negative relationship between gender diversity and dividend announcements.…”
Section: Board Gender Diversity and Dividend Payoutsmentioning
confidence: 91%
See 1 more Smart Citation
“…We used the Shannon index-SI (Shannon, 1948) as a comprehensive and superior measure of BGD, following the literature (Sial et al, 2018;Ain et al, 2021). In addition, consistent with previous studies (Liu et al, 2014;Trinh et al, 2020), we measured BGD using the Blau index-BI (Blau, 1977), a female director dummy (FDM), and the percentage of female directors (FDBD) for robustness checks. The Shannon index and Blau index (similar to the two widely used measures of diversification in the area of economics and financial studies, i.e., the entropy index and the Herfindahl-Hirschman index, respectively) are the two composite measures of BGD indicating that whether or not the boards are diverse in term of gender and produce the similar results, but the former are larger than the latter (Abad et al, 2017).…”
Section: Board Gender Diversitymentioning
confidence: 99%
“…On the basis of above arguments, some studies have examined the influence of female directors' participation on agency problems, for example, Jurkus et al (2011), Chen et al (2017), and Byoun et al (2016) in the U.S. setting; Ain et al (2020) and McGuinness et al (2015) using Chinese data 2 ; Pucheta-Martinez and Bel-Oms (2016) using data for Spanish firms; Saeed and Sameer (2017) studying emerging economies 3 ;and Trinh et al (2020) using U.K. data. These studies suggest that female participation on the board has an impact on dividend payouts but provide mixed results.…”
Section: Research-article20212021mentioning
confidence: 99%